Islamic Values and Local Wisdom: Ruwahan Tradition as a Medium for Nurturing Harmony and Tolerance - Ulum, Khozainul; Amalia, Dini (Proceedings of Annual Conference for Muslim Scholars, 2024)
This research explores the integration of Islamic values and local wisdom within Ruwahan tradition in Lamongan, a communal ritual held in the month of Sha’ban to honor ancestors and prepare spiritually for Ramadan. Through this tradition, Islamic teachings of compassion, respect, and communal solidarity are seamlessly intertwined with Javanese cultural customs, forming a harmonious blend of religious devotion and local heritage. By examining this integration, the research highlights the pivotal role of local wisdom in promoting peaceful coexistence and reinforcing Islamic values within diverse communities. Using an ethnographic approach, this qualitative research provides an in-depth understanding of Ruwahan ritual, its representation of Islamic values, and how it serves and functions as a platform for nurturing social harmony and tolerance. The findings reveal the tradition's significance and critical role in strengthening harmonious social bonds, alleviating tensions, and fostering mutual respect, tolerance, and hospitality across religious and cultural lines. They also underscore the importance of preserving and revitalizing local traditions like Ruwahan as essential vehicles for promoting Islamic values and cultivating harmony and tolerance in an increasingly pluralistic society